Perancangan Sistem Keamanan E-Monitoring Proyek Dengan Metode Agile Di PT Garda Power Mandiri - Abdullah; Dede Irawan, Rian; Yehezkiel; Djutalov, Roeslan (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
The increasing demand for efficiency and transparency in project management, particularly in the security services sector such as CCTV installation, necessitates the adoption of digital solutions. This study focuses on the design and development of an e-monitoring project report system for a company engaged in security services. The system is developed using a web-based platform and Agile methodology to ensure flexibility and adaptability. By enabling real-time project tracking, efficient reporting, and enhanced data management, the system aims to streamline operations and improve customer satisfaction. The Agile approach supports iterative development, ensuring that the system aligns with user requirements throughout the process. The results indicate a significant reduction in reporting errors, faster project completion times, and better resource management. This research contributes to advancing project management practices in security services through the integration of modern technology.